Analysis of the role of Riau Malay cultural education in improving student morale in schools - Romadon, Ahmad; Rahmatullah, M. Anas Nazarsyah; Hamidi, Anusirwan; Siregar, Rozi; Yasnel, Yasnel (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2026)
Local cultural education plays a strategic role in shaping students’ character and moral values, particularly in societies with strong cultural traditions such as the Malay community of Riau. This study aims to analyze the role of Riau Malay cultural education in enhancing students’ moral development through the integration of cultural values into the curriculum, extracurricular activities, school environment, and the roles of teachers and the community. This research employs a qualitative approach using literature review and descriptive analysis. The findings indicate that Riau Malay cultural education contributes significantly to students’ moral development through the internalization of traditional values, habituation of polite behavior, respect for parents and teachers, and the strengthening of cultural identity. The discussion highlights that teachers, families, and the surrounding environment are key determinants of successful cultural education implementation. The novelty of this study lies in its comprehensive framework that positions local cultural values not only as moral guidance but also as a strategic foundation for character education policy. The findings provide practical implications for policymakers and educators in developing culturally responsive education models that support moral education while preserving local wisdom in the era of globalization.